Quilombo do Cumbe-CE: um olhar acerca das implicações do processo Nº 0800097-05.2018.4.05.8101 no reconhecimento da identidade quilombola - Lima, Thais Kétura Borges de (Universidade Federal Rural do Semi-Árido, 2019)
This work is dedicated to analyze the implications of Process No. 0800097-05.2018.4.05.8101 in the face of the self-definition of the Community of the Cumbe-CE as remnant of quilombo. Starting from a theoretical view that considers as main identity aspects of traditional communities the preservation of the territory, the collective way of life and the guarantee of the continuity of the territorial link. The legal framework of the research is article 68 of the Transitory Provisions Act of the Federal Constitution of 1988 and Decree No. 4.887/2003, which regulate the demarcation of quilombola territories. The methodologies used were participant observation, participant observation, the use of semi-structured interviews, as well as research of historical and academic sources around the territory. In this work, the historical elements of the formation of the Cumbe-CE community are briefly presented, as well as the context from which emerged Process No. 0800097-05.2018.4.05.8101. Finally, we analyze the arguments in dispute within the scope of the aforementioned process in comparison to the theoretical construction of the quilombola right and the impressions of the residents of the Cumbe, concluding that the interpretative approach adopted in the main arguments formulated by the author of the Process No. 0800097-05.2018 .4.05.8101 remain outdated.
Monografia
Keywords: Quilombo; Identidade Quilombola; Decreto 4.887/03; Cumbe/CE; Quilombo; Quilombola identity; Decree 4.887/03; Cumbe/CE; CIENCIAS SOCIAIS APLICADAS::DIREITO